2020
DOI: 10.26656/fr.2017.4(s5).006
|View full text |Cite
|
Sign up to set email alerts
|

Alginate encapsulation of Trichoderma harzianum against brown spot disease on rice (Oryzae sativa) in vivo assays

Abstract: Bipolaris oryzae causes brown spot disease which is one of the most devastating diseases in rice. Nowadays, biological methods are effective controls which need to be developed in order to use less chemical control. Therefore, the objectives of the present study were to characterize the B. oryzae as a biocontrol agent and to measure the performance of encapsulated T. harzianum in controlling brown spot disease. Bipolaris oryzae was characterized based on morphological characteristics and alginate encapsulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many research results showed that T. harzianum pellets can suppress the attack of various pathogenic fungi such as Fusarium oxysporum f. sp. lycopersici causing wilt disease on tomatoes 6 and Helminthosporium oryzae causing brown spots on rice 7 . This study aimed to determine the ability of T. harzianum alginate pellets with rice bran in suppressing S. rolfsii attacks on chilli plants and the effect of T. harzianum pellet storage time on S. rolfsii attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Many research results showed that T. harzianum pellets can suppress the attack of various pathogenic fungi such as Fusarium oxysporum f. sp. lycopersici causing wilt disease on tomatoes 6 and Helminthosporium oryzae causing brown spots on rice 7 . This study aimed to determine the ability of T. harzianum alginate pellets with rice bran in suppressing S. rolfsii attacks on chilli plants and the effect of T. harzianum pellet storage time on S. rolfsii attacks.…”
Section: Introductionmentioning
confidence: 99%